Academic coaching: Insights from the medical student's perspective. (1st February 2020) - Wolff, Margaret; Morgan, Helen; Jackson, Jasmyne; Skye, Eric; Hammoud, Maya; Ross, Paula T.
Abstract: Purpose: With the growing recognition of the role of coaching in competency-based medical education, many medical education training programs are investing significant resources into developing coaching programs. However, there is a lack of rigorous research on academic coaching programs in medical education and recommended coaching practices are based on expert opinion without incorporating the student perspective. The aim of this study was to investigate factors that affect a students' perception of a successful coaching experience. Materials and method: This was a qualitative study performed in November 2018 at a medical school in the United States with a formal coaching program. Appreciative inquiry was the theoretical framework used to develop the question guide. The authors facilitated two focus groups and then used Colaizzi's phenomenological analysis approach to analyze the transcripts. Results: A total of 21 students participated in the focus groups. The analysis revealed four themes that describe students' perceptions of successful coaching experiences: coach attributes, relational skills, coaching skills, and utilization of coaching. Each of these themes had specific dimensions. Conclusions: The findings from this study illuminate the student stakeholder perspectives on successful coaching relationships, and should be considered when developing a coaching program and faculty development.